Solid battery and method for manufacturing solid battery

By integrating a resin current collector with an intermediate layer in solid-state batteries, the issue of active material peeling is addressed, enhancing cycle characteristics and battery durability.

JP2025008299AActive Publication Date: 2025-01-20TOYOTA JIDOSHA KK
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023110341
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-04
Publication Date
2025-01-20
Estimated Expiration
2043-07-04

AI Technical Summary

Technical Problem

Conventional solid-state batteries with ceramic or metal foils as current collectors face issues with active material peeling due to expansion and contraction during charging and discharging, leading to deteriorated cycle characteristics.

Method used

Incorporation of a resin current collector with a conductive material and an intermediate layer containing components from both the active material and resin current collector, with specific thickness ratios and expansion coefficients, to enhance compatibility and anchor effect.

Benefits of technology

The solution effectively suppresses peeling of the active material layer, thereby improving cycle characteristics and maintaining battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025008299000002
    Figure 2025008299000002
  • Figure 2025008299000003
    Figure 2025008299000003
  • Figure 2025008299000004
    Figure 2025008299000004
Patent Text Reader

Abstract

To provide a solid battery for suppressing lowering of cycle characteristics and a method for manufacturing the solid battery.SOLUTION: There are provided a solid battery including an electrode which includes a resin current collector containing a resin and a conductive material, an active substance layer containing an active substance, and an intermediate layer that is interposed between the active substance layer and the resin current collector, where at least one kind of component contained in the active substance layer and at least one kind of component contained in the resin current collector are mixed; and a method for manufacturing the solid battery.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a solid-state battery and a method for manufacturing a solid-state battery. [Background technology]

[0002] 2. Description of the Related Art In recent years, secondary batteries such as lithium-ion secondary batteries have been suitably used as portable power sources for personal computers, mobile terminals, and the like, and as power sources for driving vehicles such as electric vehicles (EVs), hybrid vehicles (HVs), and plug-in hybrid vehicles (PHVs), among others.

[0003] Secondary batteries use electrolytes that contain flammable organic solvents, so they require the installation of safety devices to suppress temperature rises in the event of a short circuit, as well as improvements to the structure and materials to prevent short circuits. In contrast, solid-state batteries, which use solid electrolyte layers to solidify the materials, do not use flammable organic solvents inside the battery, so safety devices can be simplified and they are thought to be superior in terms of manufacturing costs and productivity. For the current collector of a conventional solid-state battery, a single-layer structure made of ceramic foil or metal foil, or a laminate containing ceramic foil and metal foil has been adopted (for example, Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2007-329004 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, in a solid-state battery equipped with a current collector containing a conventional ceramic foil or metal foil, when the active material layer expands or contracts due to a sudden increase or release of the active material during charging and discharging, the active material layer may peel off from the current collector, which may result in a decrease in cycle characteristics (e.g., capacity retention rate after 50 cycles). In view of the above circumstances, an object of the present disclosure is to provide a solid-state battery that suppresses deterioration of cycle characteristics and a method for manufacturing the solid-state battery. [Means for solving the problem]

[0006] Means for solving the above problems include the following means. <1> A resin collector including a resin and a conductive material; An active material layer including an active material; and an intermediate layer interposed between the active material layer and the resin current collector, in which at least one component contained in the active material layer and at least one component contained in the resin current collector are mixed; A solid-state battery comprising an electrode having the <2> The thickness of the intermediate layer relative to the thickness of the resin collector (intermediate layer / resin collector) is 1 / 30 or more and 1 / 6 or less. <1> The solid-state battery according to claim 1, <3> The active material includes a Si-based active material. <1> or <2> The solid-state battery according to claim 1, <4> The resin collector has a linear expansion coefficient of 200×10 -6 ppm / K or more 350×10 -6 ppm / K or less. <1> ~ <3> 13. The solid-state battery according to claim 12, <5> A solid electrolyte layer including a solid electrolyte is provided. The softening temperature of the resin is equal to or lower than the crystallization temperature of the solid electrolyte. <1> ~ <4> 13. The solid-state battery according to claim 12, <6> The conductive material includes vapor grown carbon fiber (VGCF). <1> ~ <5> 13. The solid-state battery according to claim 12, <7> 1. A method for manufacturing a solid-state battery, comprising: pressing a laminate in which a resin current collector containing a thermoplastic resin and a conductive material and an active material layer containing an active material are laminated together at a temperature equal to or higher than the softening temperature of the thermoplastic resin to produce an electrode. Effect of the Invention

[0007] According to the present disclosure, there are provided a solid-state battery that suppresses deterioration of cycle characteristics and a method for manufacturing a solid-state battery. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a cross-sectional view showing one embodiment of a solid-state battery according to the present disclosure. [Diagram 2] FIG. 2 is a graph showing the relationship between the baffling pressure fluctuation value and the charge amount in Example 1 and Comparative Example 1. [Diagram 3] FIG. 3 is a graph showing the relationship between the discharge capacity and the number of charge / discharge cycles in Example 1 and Comparative Example 1. [Figure 4] FIG. 4 is a graph showing the relationship between the relative resistance value and the thickness of the intermediate layer in the solid-state batteries of Example 1, Example 2, and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, an embodiment that is an example of the present disclosure will be described. These descriptions and examples are intended to illustrate the embodiment, and are not intended to limit the scope of the present disclosure.

[0010] In the present disclosure, a numerical range expressed using "to" means a range that includes the numerical values ​​before and after "to" as the lower and upper limits. In the present disclosure, in the ranges of numerical values ​​described stepwise, the upper limit or lower limit of one numerical range may be replaced with the upper limit or lower limit of another numerical range of numerical values ​​described stepwise. In addition, in the ranges of numerical values ​​described in the present disclosure, the upper limit or lower limit of the numerical range may be replaced with a value shown in the examples. In the present disclosure, when a plurality of substances corresponding to each component are present in the composition, the amount of each component in the composition means the total amount of the plurality of substances present in the composition, unless otherwise specified. In the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments. In the description of groups (atomic groups) in the present disclosure, a description without specifying whether substituted or unsubstituted includes both those containing no substituents and those containing a substituent. In this disclosure, the term "layer" includes cases where the layer is formed over the entire area when the area in which the layer exists is observed, as well as cases where the layer is formed over only a portion of the area. In the present disclosure, the term "process" refers not only to an independent process, but also to a process that cannot be clearly distinguished from other processes, as long as the intended purpose of the process is achieved.

[0011] -Solid battery- The solid-state battery according to the present disclosure is a solid-state battery including a resin current collector containing a resin and a conductive material, an active material layer containing an active material, and an electrode having an intermediate layer interposed between the active material layer and the resin current collector and containing a mixture of at least one component contained in the active material layer and at least one component contained in the resin current collector. According to the present disclosure, the deterioration of cycle characteristics (for example, capacity retention rate after 50 cycles) is suppressed. The mechanism of this action is not necessarily clear, but is presumed to be as follows. The electrode of the solid-state battery according to the present disclosure has an intermediate layer between the resin current collector and the active material layer. The intermediate layer is a mixture of at least one component contained in the active material layer and at least one component contained in the resin current collector, and therefore has good compatibility with both the resin current collector and the active material layer, and the various components contained in the intermediate layer are mixed together to provide an anchor effect. As a result, it is believed that peeling of the active material layer from the resin current collector due to expansion and contraction of the active material layer during battery operation is suppressed, and deterioration of cycle characteristics is suppressed.

[0012] Hereinafter, "an electrode having a resin current collector containing a resin and a conductive material, an active material layer containing an active material, and an intermediate layer interposed between the active material layer and the resin current collector and containing a mixture of at least one component contained in the active material layer and at least one component contained in the resin current collector" is referred to as a "specific electrode".

[0013] The solid-state battery of the present disclosure includes a so-called all-solid-state battery using a solid electrolyte as an electrolyte, and the solid electrolyte may contain an electrolytic solution in an amount of less than 10 mass% based on the total amount of the electrolyte. The solid electrolyte may be a composite solid electrolyte containing an inorganic solid electrolyte and a polymer electrolyte.

[0014] An example of the solid-state battery of the present disclosure will be described with reference to the drawings. FIG. 1 is a schematic cross-sectional view showing an example of the solid-state battery of the present disclosure. The solid-state battery shown in FIG. 1 includes an anode including an anode current collector 113 and an anode active material layer A, a solid electrolyte layer B, and a cathode including a cathode current collector 115 and a cathode active material layer C. The anode active material layer A includes an anode active material 101, a conductive assistant 105, a binder 109, and a solid electrolyte 102. The cathode active material layer C includes a cathode active material 103, a conductive assistant 107, a binder 111, and a solid electrolyte 102. The solid electrolyte layer B may have a single layer or a two-layer structure.

[0015] The solid-state battery shown in Fig. 1 may include the specific electrode as at least one of the negative and positive electrodes. When the negative electrode is the specific electrode, the negative electrode current collector 113 is a resin current collector containing resin and a conductive material. When the positive electrode is the specific electrode, the positive electrode current collector 115 is a resin current collector containing resin and a conductive material.

[0016] When a set of a positive electrode, a solid electrolyte layer, and a negative electrode is defined as a power generation unit, the solid-state battery may have only one power generation unit or may have two or more power generation units. When the solid-state battery has two or more power generation units, the power generation units may be connected in series or in parallel.

[0017] When the solid-state battery has two or more power generation units (i.e., when it is a stacked-type battery), it is sufficient that at least one positive electrode or negative electrode is a specific electrode. From the viewpoint of further suppressing deterioration of cycle characteristics, it is preferable that the electrode located in the middle of the stacked structure (for example, in the case of a monopolar type, the "positive electrode active material layer / current collector / positive electrode active material layer" and / or the "negative electrode active material layer / current collector / negative electrode active material layer" portion of a stacked battery of "negative electrode active material layer / current collector / positive electrode active material layer / solid electrolyte layer / positive electrode active material layer / current collector / positive electrode active material layer" and in the case of a bipolar type, the "positive electrode active material layer / current collector" and / or the "current collector / negative electrode active material layer" portion of a stacked battery of "negative electrode active material layer / current collector / positive electrode active material layer / solid electrolyte layer / negative electrode active material layer / current collector / positive electrode active material layer") is a specific electrode, and it is preferable that the electrodes in all the power generation units are specific electrodes.

[0018] In the solid-state battery, the stacking end faces (i.e., side faces) of the stacking structure of the positive electrode / solid electrolyte layer / negative electrode may be sealed with a sealant such as resin. The negative electrode current collector 113 and the positive electrode current collector 115 may have a buffer layer, an elastic layer, or a PTC (Positive Temperature Coefficient) thermistor layer disposed on the outer circumferential surface. The shape of the solid-state battery is not particularly limited, and may be, for example, a coin type, a cylindrical type, a square type, a sheet type, a button type, a flat type, or a laminate type.

[0019] <Specific electrode> The specific electrode is an electrode having a resin current collector containing a resin and a conductive material, an active material layer containing an active material, and an intermediate layer interposed between the active material layer and the resin current collector, in which at least one component contained in the active material layer and at least one component contained in the resin current collector are mixed.

[0020] The solid-state battery according to the present disclosure may include the specific electrode as at least one of the negative electrode and the positive electrode. For example, from the viewpoint of further suppressing the deterioration of cycle characteristics, the solid-state battery according to the present disclosure preferably includes the specific electrode as the negative electrode, and more preferably includes the specific electrode as both the negative electrode and the positive electrode.

[0021] [Resin current collector] The resin current collector includes a resin and a conductive material. Examples of the resin include known thermoplastic resins such as poly(meth)acrylic acid, polymethyl(meth)acrylate, polyethylene, polypropylene, polyethylene terephthalate, polyether nitrile, polyimide, polyamide, polytetrafluoroethylene, polyacrylonitrile, poly(meth)acrylate, and halogenated vinyl resin; thermosetting resins such as epoxy resin, vinyl ester resin, unsaturated polyester resin, phenol resin, and melamine resin; and known conductive polymers such as polyaniline, polypyrrole, polythiophene, polyacetylene, polyparaphenylene, polyphenylenevinylene, polyacrylonitrile, and polyoxadiazole. The resin may be used alone or in combination of two or more kinds. Among the above, from the viewpoint of further suppressing peeling of the active material layer from the resin current collector and deterioration of the cycle characteristics, the resin preferably contains at least one of a thermoplastic resin and a conductive polymer, more preferably contains a thermoplastic resin, and further preferably contains one type of resin selected from the group consisting of polymethyl(meth)acrylate, poly(meth)acrylic acid, and polyacrylonitrile.

[0022] In the present disclosure, the term "(meth)acrylic acid" refers to a concept that includes both acrylic acid and methacrylic acid, and the term "(meth)acrylate" refers to a concept that includes both acrylate and methacrylate.

[0023] The resin may be a crystalline resin, an amorphous resin, or a mixture of both, and is preferably an amorphous resin from the viewpoint of increasing strength and suppressing the active material layer from peeling off from the resin current collector and the deterioration of cycle characteristics. The "crystalline" resin refers to the presence of an endothermic peak with a half-width of 10°C or less when measured at a heating rate of 10 (°C / min) in differential scanning calorimetry (DSC measurement). On the other hand, the "amorphous" resin refers to the half-width exceeding 10°C, or the absence of a clear endothermic peak.

[0024] The softening temperature of the resin varies depending on the type of resin, but from the viewpoint of the strength of the resin current collector and the suppression of deterioration of the active material, the softening temperature of the resin is preferably equal to or lower than the crystallization temperature of the solid electrolyte contained in the solid electrolyte layer described later. The softening temperature of the resin is determined from a DSC curve obtained by differential scanning calorimetry (DSC).

[0025] Examples of the conductive material include carbon materials, conductive polymers, metal particles, etc. The conductive material may be used alone or in combination of two or more kinds. Examples of carbon materials include particulate carbon materials, fibrous carbon materials, etc. Examples of particulate carbon materials include acetylene black (AB), ketjen black (KB), etc. Examples of fibrous carbon materials include carbon nanotubes (CNT), carbon nanofibers (CNF), vapor grown carbon fibers (VGCF), etc. Examples of the conductive polymer include polythiophene, polyacetylene, polyparaphenylene, and polyisothianaphthene. Metal particles include nickel, copper, iron, stainless steel, and the like particles. Among the above, from the viewpoint of enhancing the anchor effect and further suppressing peeling of the active material layer from the resin current collector and deterioration of cycle characteristics, it is preferable that the conductive material contains a carbon material, more preferably contains at least one of acetylene black (AB) and vapor grown carbon fiber (VGCF), and even more preferably contains vapor grown carbon fiber (VGCF).

[0026] The content of the conductive material is preferably 10% by mass or more and 50% by mass or less, more preferably 15% by mass or more and 43% by mass or less, and even more preferably 15% by mass or more and 35% by mass or less, based on the total solid content of the resin collector.

[0027] From the viewpoint of preventing the active material layer from peeling off from the resin current collector and the deterioration of cycle characteristics, the resin current collector should have a linear expansion coefficient of 100×10 -6 ppm / K or more 500×10-6 It is preferable that the concentration is less than 200×10 ppm / K. -6 ppm / K or more 430×10 -6 More preferably, it is 230×10 ppm / K or less. -6 ppm / K or more 350×10 -6 It is more preferable that the coefficient of linear expansion is not more than ppm / K. The value of the linear expansion coefficient is a value measured by a method in accordance with JIS H7404-1993.

[0028] There are no particular limitations on the method for setting the linear expansion coefficient of the resin current collector within the above range, and examples thereof include a method in which the resin in the resin current collector is one of the above-mentioned suitable resins.

[0029] The thickness of the resin current collector is not particularly limited, but from the viewpoint of further suppressing the deterioration of cycle characteristics due to peeling of the intermediate layer or active material layer from the resin current collector, the thickness is preferably 5 μm or more and 80 μm or less, more preferably 10 μm or more and 50 μm or less, and even more preferably 10 μm or more and 30 μm or less.

[0030] The thickness of the resin current collector was determined by observing a cross section of the resin current collector cut in the thickness direction using a scanning electron microscope (SEM) equipped with an energy dispersive X-ray spectrometer (EDX) and measuring the thickness at any ten points, and averaging the thicknesses.

[0031] The method for forming the resin current collector is not particularly limited, and examples thereof include a method in which, when the resin is thermoplastic, a coating liquid containing the resin and a conductive material is applied, dried, and molded; and, when the resin is thermosetting, a method in which raw materials such as a resin precursor or a monomer and a conductive material are placed in a mold and heated to solidify.

[0032] The resin current collector may further contain other materials in addition to the resin, the spherical carbon material, and the fibrous carbon, such as a binder and a metal powder material.

[0033] [Active material layer] The active material layer contains an active material. Preferred aspects of the active material vary depending on whether the active material is a negative electrode or a positive electrode, and will be described later in the sections for the negative electrode and the positive electrode, respectively.

[0034] The active material may include a Si-based active material. The Si-based active material is a useful active material with excellent charge / discharge characteristics. However, the Si-based active material tends to expand and contract significantly during charging and discharging, which causes the active material layer to easily peel off from the current collector and the cycle characteristics to easily deteriorate. On the other hand, as described above, the solid-state battery according to the present disclosure has an intermediate layer between the resin current collector and the active material layer in the electrode, so that the deterioration of the cycle characteristics caused by the active material layer peeling off from the resin current collector is also suppressed. This is more effective when the battery contains a Si-based active material.

[0035] The Si-based active material is not particularly limited as long as it contains silicon and can act as an active material, and examples thereof include silicon particles, silicon alloy particles (e.g., alloys of Si and one or more metals selected from the group consisting of Sn, Ti, Fe, Ni, Cu, Co, and Al), porous silicon, silicon clathrate compounds, silicon oxides, and mixtures thereof. The Si-based active material may be one type alone or two or more types in combination.

[0036] The thickness of the active material layer is not particularly limited, but from the viewpoint of, for example, achieving better charge / discharge characteristics and further suppressing peeling of the active material layer from the resin current collector and a decrease in cycle characteristics, the thickness is preferably 0.1 μm or more and 100.0 μm or less, preferably 1.0 μm or more and 100.0 μm or less, and more preferably 30.0 μm or more and 100.0 μm or less.

[0037] The thickness of the active material layer is the average value of thicknesses measured at any ten points on a cross section of the active material layer cut in the thickness direction using a scanning electron microscope (SEM) equipped with an energy dispersive X-ray spectrometer (EDX).

[0038] [Middle class] The intermediate layer is a layer in which at least one component contained in the active material layer and at least one component contained in the resin current collector are mixed. From the viewpoint of enhancing the anchor effect and further reducing peeling of the active material layer from the resin current collector, it is preferable that the intermediate layer is a layer in which at least the active material contained in the active material layer and the resin contained in the resin current collector are mixed.

[0039] From the viewpoint of enhancing the anchor effect and further reducing peeling of the active material layer from the resin current collector, the thickness of the intermediate layer relative to the thickness of the resin current collector (intermediate layer / resin current collector) is preferably 1.0 / 30.0 or more and 1.0 / 4.0 or less, more preferably 1.0 / 20.0 or more and 1.0 / 5.0 or less, and even more preferably 1.0 / 10.0 or more and 1.0 / 6.0 or less.

[0040] The thickness of the intermediate layer is not particularly limited, but from the viewpoint of, for example, achieving better charge / discharge characteristics and further suppressing peeling of the active material layer from the resin current collector and a decrease in cycle characteristics, the thickness is preferably 0.1 μm or more and 15.0 μm or less, more preferably 0.4 μm or more and 10.0 μm or less, and even more preferably 0.6 μm or more and 8.0 μm or less.

[0041] The thickness of the intermediate layer is determined by observing a cross section of the intermediate layer cut in the thickness direction using a scanning electron microscope (SEM) equipped with an energy dispersive X-ray spectrometer (EDX) and averaging the thicknesses measured at any ten points. The components contained in the intermediate layer can be confirmed by EDX analysis of the chemical composition of a laminate cross section cut in the thickness direction of the intermediate layer using a scanning electron microscope (SEM) equipped with an energy dispersive X-ray spectrometer (EDX).

[0042] The method for forming the intermediate layer is not particularly limited, and examples thereof include: 1) when the resin in the resin current collector is thermoplastic, a method including a step of heating a laminate in which a resin current collector containing a thermoplastic resin (which may further contain a conductive material) and an active material layer containing an active material are laminated to a temperature equal to or higher than the softening temperature of the thermoplastic resin, and pressing the laminate; and 2) when the resin in the resin current collector is thermosetting, a method of molding by filling a precursor of a thermosetting resin and components such as an active material and a binder in the active material layer into a mold and heating the mold.

[0043] Hereinafter, each component of the solid-state battery, such as the negative electrode, the positive electrode, and the solid electrolyte layer, will be described in detail.

[0044] <Negative electrode> The negative electrode is a layer having a negative electrode current collector and a negative electrode active material layer that is provided on the negative electrode current collector and contains a negative electrode active material. When the negative electrode is a specific electrode, the negative electrode current collector refers to a resin current collector, and an intermediate layer in which at least one component contained in the active material layer and at least one component contained in the resin current collector are mixed is interposed between the active material layer and the resin current collector.

[0045] When the negative electrode is not a specific electrode, examples of the material for the negative electrode current collector include stainless steel, copper, nickel, carbon, etc. Examples of the shape of the negative electrode current collector include a foil shape and a mesh shape.

[0046] Examples of the negative electrode active material include carbon materials such as graphite, hard carbon, soft carbon, and carbon nanotubes; and Si-based active materials.

[0047] The negative electrode active material layer may further contain a solid electrolyte, a binder, and the like in addition to the negative electrode active material, as necessary.

[0048] Examples of the solid electrolyte include the same solid electrolytes as those exemplified as the solid electrolyte that can be contained in the solid electrolyte layer. Examples of the binder include rubber-based binders, fluoride-based binders, etc. Examples of the rubber-based binders include butadiene rubber, hydrogenated butadiene rubber, styrene butadiene rubber (SBR), hydrogenated styrene butadiene rubber, nitrile butadiene rubber, hydrogenated nitrile butadiene rubber, ethylene propylene rubber, etc. Examples of the fluoride-based binders include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-polyhexafluoropropylene copolymer (PVDF-HFP), polytetrafluoroethylene, fluororubber, etc.

[0049] <Positive electrode> The positive electrode is, for example, a layer having a positive electrode current collector and a positive electrode active material layer that is provided on the positive electrode current collector and contains a positive electrode active material. When the positive electrode is a specific electrode, the positive electrode current collector refers to a resin current collector, and an intermediate layer in which at least one component contained in the active material layer and at least one component contained in the resin current collector are mixed is interposed between the active material layer and the resin current collector.

[0050] When the positive electrode is not a specific electrode, examples of the material for the positive electrode current collector include stainless steel, aluminum, nickel, iron, titanium, carbon, etc. Examples of the shape of the positive electrode current collector include a foil shape and a mesh shape.

[0051] The positive electrode active material preferably contains a lithium composite oxide. The lithium composite oxide may contain at least one selected from the group consisting of F, Cl, N, S, Br, and I. The lithium composite oxide may have a crystal structure belonging to at least one space group selected from the space groups R-3m, Immm, and P63-mmc (also called P63mc or P6 / mmc). The lithium composite oxide may have an O2 type structure in which the transition metal, oxygen, and lithium are mainly arranged. Examples of lithium composite oxides having a crystal structure belonging to R-3m include Li x Me y O α X β(Me represents at least one selected from the group consisting of Mn, Co, Ni, Fe, Al, Cu, V, Nb, Mo, Ti, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, Ag, Ru, W, B, Si, and P, and X represents at least one selected from the group consisting of F, Cl, N, S, Br, and I, satisfying 0.5 ≦ x ≦ 1.5, 0.5 ≦ y ≦ 1.0, 1 ≦ α < 2, and 0 < β ≦ 1.) Compounds represented thereby are exemplified. Examples of the lithium composite oxide having a crystal structure belonging to Immm include, for example, Li x1 M 1 A 1 2 (satisfying 1.5 ≦ x1 ≦ 2.3, M 1 includes at least one selected from the group consisting of Ni, Co, Mn, Cu, and Fe, and A 1 includes at least oxygen, and the ratio of oxygen in A 1 is 85 atomic% or more.) Composite oxides represented thereby (specific example: Li2NiO2), Li x1 M 1A 1-x2 M 1B x2 O 2-y A 2 y (0 ≦ x2 ≦ 0.5, 0 ≦ y ≦ 0.3, and at least one of x2 and y is not 0, M 1A represents at least one selected from the group consisting of Ni, Co, Mn, Cu, and Fe, M 1B represents at least one selected from the group consisting of Al, Mg, Sc, Ti, Cr, V, Zn, Ga, Zr, Mo, Nb, Ta, and W, and A2 represents at least one selected from the group consisting of F, Cl, Br, S, and P.) Composite oxides represented thereby are exemplified.

[0052] Examples of the lithium composite oxide having a crystal structure belonging to P63 - mmc include, for example, M1 x M2 y O2 (M1 represents an alkali metal (preferably at least one of Na and K), M2 represents a transition metal (preferably at least one selected from the group consisting of Mn, Ni, Co, and Fe), and x + y satisfies 0 < x + y ≦ 2.) Composite oxides represented thereby are exemplified.

[0053] Examples of the lithium composite oxide having an O2-type structure include, for example, Li x [Li α (Mn a Co b M c ) 1-α O2 (where 0.5 < x < 1.1, 0.1 < α < 0.33, 0.17 < a < 0.93, 0.03 < b < 0.50, 0.04 < c < 0.33, and M represents at least one selected from the group consisting of Ni, Mg, Ti, Fe, Sn, Zr, Nb, Mo, W, and Bi).) The composite oxide represented by, and specific examples include Li 0.744 [Li 0.145 Mn 0.625 Co 0.115 Ni 0.115 O2 and the like.

[0054] In addition, the positive electrode preferably contains a solid electrolyte selected from the group of solid electrolytes consisting of a sulfide solid electrolyte, an oxide solid electrolyte, and a halide solid electrolyte in addition to the positive electrode active material, and a mode in which at least a part of the surface of the positive electrode active material is coated with a sulfide solid electrolyte, an oxide solid electrolyte, or a halide solid electrolyte is more preferable. Examples of the halide solid electrolyte that coats at least a part of the surface of the positive electrode active material include Li 6-(4-x)b (Ti 1-x Al x ) b F6 (0 < x < 1, 0 < b ≤ 1.5) [LTAF electrolyte] is preferable.

[0055] The positive electrode may further contain a solid electrolyte, a binder, etc. in addition to the positive electrode active material, if necessary.

[0056] The solid electrolyte preferably contains at least one solid electrolyte selected from the group of solid electrolytes consisting of a sulfide solid electrolyte, an oxide solid electrolyte, and a halide solid electrolyte. The positive electrode preferably has a mode in which at least a part of the surface of the positive electrode active material is coated with a sulfide solid electrolyte, an oxide solid electrolyte, or a halide solid electrolyte. As the halide solid electrolyte that coats at least a part of the surface of the positive electrode active material, Li 6-(4-x)b (Ti 1-x Al x ) b F6 (0 < x < 1, 0 < b ≤ 1.5) [LTAF electrolyte] is preferred.

[0057] Examples of the binder include the same ones as those exemplified as the binder that can be included in the negative electrode.

[0058] <Solid electrolyte layer> The solid electrolyte layer contains a solid electrolyte. From the viewpoint of battery performance, the solid electrolyte preferably contains at least one solid electrolyte species selected from the group of solid electrolytes consisting of sulfide solid electrolytes, oxide solid electrolytes, and halide solid electrolytes, and more preferably contains a sulfide solid electrolyte. As the sulfide solid electrolyte, it is preferable to contain sulfur (S) as the main component of the anion element, and it is preferable to further contain, for example, Li element and A element in addition to S. The A element is at least one selected from the group consisting of P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In. The sulfide solid electrolyte may further contain at least one of O and halogen elements. Examples of the halogen element (X) include F, Cl, Br, I, etc. The composition of the sulfide solid electrolyte is not particularly limited, and examples include xLi2S·(100 - x)P2S5 (70 ≤ x ≤ 80), yLiI·zLiBr·(100 - y - z)(xLi2S·(1 - x)P2S5) (0.7 ≤ x ≤ 0.8, 0 ≤ y ≤ 30, 0 ≤ z ≤ 30). The sulfide solid electrolyte may have a composition represented by the following general formula (1). Li 4-x Ge 1-x P x S4 (0 < x < 1) ··· Formula (1) In formula (1), at least a part of Ge may be substituted with at least one selected from the group consisting of Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V, and Nb. Further, at least a part of P may be substituted with at least one selected from the group consisting of Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V, and Nb. A part of Li may be substituted with at least one selected from the group consisting of Na, K, Mg, Ca, and Zn. A part of S may be substituted with a halogen. The halogen is at least one of F, Cl, Br, and I. As the oxide solid electrolyte, it is preferable to contain oxygen (O) as the main component of the anion element. For example, it may contain Li, Q element (Q represents at least one of Nb, B, Al, Si, P, Ti, Zr, Mo, W, and S), and O. Examples of the oxide solid electrolyte include garnet-type solid electrolytes, perovskite-type solid electrolytes, NASICON-type solid electrolytes, Li-P-O-based solid electrolytes, Li-B-O-based solid electrolytes, etc. Examples of the garnet-type solid electrolyte include, for example, Li7La3Zr2O 12 、Li 7-x La3(Zr 2-x Nb x )O 12 (0 ≦ x ≦ 2), Li5La3Nb2O 12 and the like. Examples of the perovskite-type solid electrolyte include, for example, (Li, La)TiO3, (Li, La)NbO3, (Li, Sr)(Ta, Zr)O3, etc. Examples of the NASICON-type solid electrolyte include, for example, Li(Al, Ti)(PO4)3, Li(Al, Ga)(PO4)3, etc. Examples of the Li-P-O-based solid electrolyte include Li3PO4, LIPON (a compound in which a part of O in Li3PO4 is substituted with N), and examples of the Li-B-O-based solid electrolyte include Li3BO3, a compound in which a part of O in Li3BO3 is substituted with C, etc. As the halide solid electrolyte, a solid electrolyte containing Li, M, and X (M represents at least one of Ti, Al, and Y, and X represents F, Cl, or Br) is suitable. Specifically, Li 6-3z Y z X6 (X represents Cl or Br, and z satisfies 0 < z < 2), Li6-(4-x)b (Ti 1-x Al x ) b F6 (0 < x < 1, 0 < b ≤ 1.5) is preferred. Li 6-3z Y z Among LiX6, Li3YX6 (where X represents Cl or Br) is more preferred and Li3YCl6 is even more preferred in terms of excellent lithium ion conductivity. Also, Li 6-(4-x)b (Ti 1-x Al x ) b F6 (0 < x < 1, 0 < b ≤ 1.5) is preferably included together with a solid electrolyte such as a sulfide solid electrolyte, for example, from the viewpoint of suppressing oxidative decomposition of the sulfide solid electrolyte.

[0059] The crystallization temperature of the solid electrolyte varies depending on the type of solid electrolyte employed. For example, it is preferably 0% or more and 90% or less, more preferably 20% or more and 85% or less, and even more preferably 50% or more and 85% or less. Note that the degree of crystallization of the solid electrolyte is a value measured by the X-ray diffraction method.

[0060] The ratio of the negative electrode active material layer to the solid electrolyte layer (negative electrode active material layer / solid electrolyte) is not particularly limited. For example, it is preferably 85 / 15 or more and 30 / 70 or less, and more preferably 80 / 20 or more and 40 / 60 or less.

[0061] The ratio of the positive electrode active material layer to the solid electrolyte layer (positive electrode active material layer / solid active material layer) is not particularly limited. For example, it is preferably 85 / 15 or more and 30 / 70 or less, and more preferably 80 / 20 or more and 50 / 50 or less.

[0062] <Outer package> The solid battery may further include an outer package. The outer package houses at least the above-described power generation unit. Examples of the outer package include a laminate type outer package and a case type outer package.

[0063] <Restraining member> The solid-state battery may further include a restraining member. The restraining member applies a restraining pressure to the positive electrode, the solid electrolyte layer, and the negative electrode in the thickness direction. The restraining pressure is preferably 0.1 MPa or more, more preferably 1 MPa or more, and even more preferably 5 MPa or more. The restraining pressure is preferably 100 MPa or less, more preferably 50 MPa or less, and even more preferably 20 MPa or less. The restraining pressure is preferably 0.1 MPa to 100 MPa.

[0064] <Application> The solid-state battery of the present disclosure is a typical solid-state secondary battery (more preferably a solid-state lithium-ion secondary battery). Examples of the solid-state battery include power sources for vehicles, electronic devices, and electric storage. Examples of the vehicle include electric four-wheeled vehicles, electric two-wheeled vehicles, gasoline automobiles, and diesel automobiles. Examples of the electric four-wheeled vehicles include electric vehicles (BEVs), plug-in hybrid vehicles (PHEVs), and hybrid vehicles (HEVs). Examples of the electric two-wheeled vehicles include electric motorcycles and power-assisted bicycles. Examples of the electronic devices include handheld devices (e.g., smartphones, tablet computers, audio players, etc.), portable devices (e.g., notebook computers, CD (Compact Disc) players, and movable devices (e.g., power tools, commercial video cameras, etc.). Among these, the solid-state battery of the present disclosure is preferably used as a power source for driving hybrid automobiles, plug-in hybrid automobiles, or electric automobiles.

[0065] -Solid-state battery manufacturing method- A method for producing a solid-state battery according to the present disclosure includes a step of pressing a laminate in which a resin current collector containing a thermoplastic resin and a conductive material and an active material layer containing an active material are laminated at a temperature equal to or higher than the softening temperature of the thermoplastic resin to produce an electrode.

[0066] In the method for producing a solid-state battery according to the present disclosure, for example, the laminate is pressed at a temperature equal to or higher than the softening temperature of the thermoplastic resin, so that the active material layer penetrates into the region of the resin current collector where the thermoplastic resin is softened, and an intermediate layer is formed between the active material layer and the resin current collector, in which at least one component contained in the active material layer and at least one component contained in the resin current collector are mixed. This intermediate layer is compatible with both the resin current collector and the active material layer, and the various components contained in the intermediate layer have an anchor effect. As a result, it is believed that peeling of the active material layer from the resin current collector due to expansion and contraction of the active material layer during battery operation is suppressed, and deterioration of cycle characteristics is suppressed.

[0067] The manufacturing method of the solid-state battery according to the present disclosure may be a manufacturing method including, for example, a step of pressing a laminate in which a resin current collector containing a thermoplastic resin and a conductive material and an active material layer containing an active material are laminated at a temperature equal to or higher than the softening temperature of the thermoplastic resin to prepare an electrode (hereinafter also referred to as an "electrode preparation step"), and a step of stacking the electrode, which is at least one of a positive electrode and a negative electrode, with a solid electrolyte layer to obtain a solid-state battery (hereinafter also referred to as a "stacking step").

[0068] <Electrode manufacturing process> In the electrode preparation process, a laminate formed by laminating a resin collector containing a thermoplastic resin and a conductive material and an active material layer containing an active material is pressed at a temperature equal to or higher than the softening temperature of the thermoplastic resin to prepare an electrode. A preferred embodiment of the resin current collector containing a thermoplastic resin and a conductive material is the same as the preferred embodiment in the above-mentioned section on the solid-state battery. A preferred embodiment of the active material layer containing an active material is the same as the preferred embodiment in the above-mentioned section on the solid-state battery.

[0069] The softening temperature of the thermoplastic resin varies depending on the thermoplastic resin used, but may be, for example, 100°C or higher and 200°C or lower, 110°C or higher and 190°C or lower, or 130°C or higher and 180°C or lower.

[0070] The heating temperature of the laminate need only be equal to or higher than the softening temperature of the thermoplastic resin. From the viewpoint of battery performance and of more efficiently producing the intermediate layer, the heating temperature is preferably equal to or higher than the softening temperature of the thermoplastic resin and not higher than the softening temperature + 100°C, more preferably equal to or higher than the softening temperature and not higher than the softening temperature + 90°C, more preferably equal to or higher than the softening temperature and not higher than the softening temperature + 80°C, and even more preferably equal to or higher than the softening temperature and not higher than the softening temperature + 75°C.

[0071] The method for pressing the laminate is not particularly limited, and may be a mode in which a laminate previously heated to a temperature equal to or higher than the softening temperature of the thermoplastic resin is pressed (i.e., heating and pressing may be separate steps), or a mode in which the laminate is pressed while being heated to a temperature equal to or higher than the softening temperature of the thermoplastic resin (i.e., heating and pressing may be simultaneous steps). From the viewpoint of production efficiency, the method for pressing the laminate is preferably a mode in which the laminate is pressed while being heated to a temperature equal to or higher than the softening temperature of the thermoplastic resin.

[0072] Examples of the pressing method include roll pressing, cold isostatic pressing (CIP), etc. The pressing pressure is not particularly limited as long as it is sufficient for the active material layer to be embedded in the resin current collector and an intermediate layer to be formed, and may be 1 kN / cm or more and 100 kN / cm or less, 5 kN / cm or more and 80 kN / cm or less, or 10 kN / cm or more and 70 kN / cm or less.

[0073] <Lamination process> In the lamination step, at least one of the positive electrode and the negative electrode and a solid electrolyte layer are laminated to obtain a solid-state battery. The electrode produced in the above-mentioned electrode production process may be used as either the positive electrode or the negative electrode. However, from the viewpoint of further suppressing a deterioration in cycle characteristics, for example, it is preferable to use the electrode produced in the above-mentioned electrode production process as the negative electrode, and it is more preferable to use the electrode as both the negative electrode and the positive electrode.

[0074] The preferred embodiment of the solid electrolyte layer is the same as the preferred embodiment in the above-mentioned section on the solid-state battery. A known method can be used to laminate the electrodes and the solid electrolyte layer.

[0075] <Other processes> The method for producing a solid-state battery according to the present disclosure may further include other steps in addition to the electrode preparation step and the lamination step, such as a step of initially charging the solid-state battery, a step of converting the solid-state battery into a bipolar solid-state battery, a step of processing the solid-state battery into a predetermined size by cutting, punching, or the like, and a step of laminating the solid-state batteries. EXAMPLES

[0076] <Example 1> [Preparation of Positive Electrode] The raw material is NCA-based positive electrode active material (LiNi 0.8 Co 0.15 Al 0.05 A positive electrode slurry was prepared by stirring a positive electrode mixture containing NCA, sulfide-based solid electrolyte (Li2S-P2S5), conductive material (VGCF), PVdF-based binder, and butyl butyrate using an ultrasonic dispersion device. The mass ratio of NCA-based positive electrode active material: sulfide-based solid electrolyte: vapor-phase grown carbon fiber: PVdF-based binder in the positive electrode slurry was adjusted to 88.2:9.8:1.3:0.7. This positive electrode slurry was applied to Al foil and SUS foil by the blade method, and these were dried at 100°C on a hot plate for 30 minutes to obtain two positive electrodes having a positive electrode active material layer.

[0077] [Preparation of negative electrode] A negative electrode slurry was prepared by stirring the negative electrode mixture containing powdered Si particles, sulfide-based solid electrolyte (Li2S-P2S5), conductive material (VGCF), PVDF-based binder, and butyl butyrate as raw materials using an ultrasonic dispersion device. The mass ratio of powdered Si particles: sulfide-based solid electrolyte: carbon material: PVDF-based binder in the negative electrode slurry was adjusted to 100:77.6:2:15. This negative electrode slurry was applied to Ni foil and SUS foil by the blade method, and these were dried at 100°C on a hot plate for 30 minutes to obtain two negative electrodes having a negative electrode active material layer.

[0078] [Preparation of solid electrolyte layer] A solid electrolyte slurry was prepared by stirring a solid electrolyte mixture containing a sulfide-based solid electrolyte (Li2S-P2S5), a PVDF-based binder, and butyl butyrate as raw materials using an ultrasonic dispersing device. The mass ratio of the sulfide-based solid electrolyte to the PVDF-based binder in the solid electrolyte slurry was adjusted to 99.4:0.4. This solid electrolyte slurry was applied by a blade method onto each of the positive electrode active material layers of the two positive electrodes prepared above, to obtain a laminate of a solid electrolyte layer / positive electrode active material layer / Al foil (solid electrolyte layer / positive electrode) and a laminate of a solid electrolyte layer / positive electrode active material layer / SUS foil (solid electrolyte layer / positive electrode).

[0079] [Preparation of resin current collector] A conductive paste containing the types and amounts of conductive materials and resins, polymethyl methacrylate (amorphous resin), and butyl butyrate shown in Table 1 was applied onto a PET film by a blade method, dried at 150°C for 30 minutes, and then the PET film was peeled off to obtain a resin current collector. The glass transition temperature (i.e., softening temperature) of the resin was lower than the crystallization temperature of the solid electrolyte.

[0080] [Preparation of Laminate] The two types of positive electrode / solid electrolyte layers and two types of negative electrodes prepared above were laminated in the following combinations to obtain two quasi-laminates. ·Ni foil / negative electrode active material layer / solid electrolyte layer / positive electrode active material layer / SUS foil ·SUS foil / negative electrode active material layer / solid electrolyte layer / positive electrode active material layer / Al foil Next, the two quasi-laminates were pressed with a roll press at a pressure of 50 kN / cm and a temperature of 160°C. Then, the SUS foil was peeled off from each of the quasi-laminates, and a resin current collector was placed between the laminates from which the SUS foil had been peeled off, to obtain a laminate having a laminated structure of "Ni foil / negative electrode active material layer / solid electrolyte layer / positive electrode active material layer / resin current collector / negative electrode active material layer / solid electrolyte layer / positive electrode active material layer / Al foil". After that, this laminate was pressed with a roll press at a pressure of 20 kN / cm and a temperature of 160°C. Next, a 1 cm 2 By punching out the resulting pieces into the desired size, a solid-state battery having a layered structure of "Ni foil / negative electrode active material layer / solid electrolyte layer / positive electrode active material layer / intermediate layer / resin current collector / intermediate layer / negative electrode active material layer / solid electrolyte layer / positive electrode active material layer / Al foil" was obtained.

[0081] <Examples 2 to 6> In the preparation of the resin current collector, a resin current collector was obtained under the same specifications as in Example 1, except that the amount of resin and the type and amount of the conductive material were set to the specifications shown in Table 1. A solid-state battery was obtained under the same specifications as in Example 1, except that the obtained resin current collector was used.

[0082] <Comparative Example 1> [Preparation of Positive Electrode] The raw material is NCA-based positive electrode active material (LiNi 0.8 Co 0.15 Al 0.05 A positive electrode slurry was prepared by stirring a positive electrode mixture containing NCA, sulfide-based solid electrolyte (Li2S-P2S5), conductive material (VGCF), PVdF-based binder, and butyl butyrate using an ultrasonic dispersion device. The mass ratio of NCA-based positive electrode active material: sulfide-based solid electrolyte: vapor-phase grown carbon fiber: PVdF-based binder in the positive electrode slurry was adjusted to 88.2:9.8:1.3:0.7. This positive electrode slurry was applied onto an Al foil by a blade method, and the resulting mixture was dried at 100°C on a hot plate for 30 minutes to obtain one positive electrode having a positive electrode active material layer.

[0083] [Preparation of negative electrode] A negative electrode slurry was prepared by stirring the negative electrode mixture containing powdered Si particles, sulfide-based solid electrolyte (Li2S-P2S5), conductive material (VGCF), PVDF-based binder, and butyl butyrate as raw materials using an ultrasonic dispersion device. Here, the mass ratio of powdered Si particles: sulfide-based solid electrolyte: carbon material: PVDF-based binder in the negative electrode slurry was adjusted to 100: 77.6: 2: 15. This negative electrode slurry was applied onto Ni foil by the blade method, and these were dried at 100 ° C on a hot plate for 30 minutes to obtain one negative electrode having a negative electrode active material layer.

[0084] [Preparation of solid electrolyte layer] A solid electrolyte slurry was prepared by stirring a solid electrolyte mixture containing a sulfide-based solid electrolyte (Li2S-P2S5), a PVDF-based binder, and butyl butyrate as raw materials using an ultrasonic dispersing device. The mass ratio of the sulfide-based solid electrolyte to the PVDF-based binder in the solid electrolyte slurry was adjusted to 99.4:0.4. This solid electrolyte slurry was applied by a blade method onto the positive electrode active material layer of the positive electrode prepared above, to obtain a laminate of the solid electrolyte layer / positive electrode active material layer / Al foil (solid electrolyte layer / positive electrode).

[0085] [Preparation of Laminate] One type of positive electrode / solid electrolyte layer prepared above and one type of negative electrode were laminated in the following combination to obtain one laminate. ·Ni foil / negative electrode active material layer / solid electrolyte layer / positive electrode active material layer / Al foil Next, the laminate was pressed with a roll press at a pressure of 50 kN / cm and a temperature of 160°C. 2 By punching out the resulting pieces into the size shown in FIG. 1, a solid-state battery having a layered structure of "Ni foil / negative electrode active material layer / solid electrolyte layer / positive electrode active material layer / Al foil" was obtained.

[0086] <Comparative Example 2> A solid-state battery was obtained under the same specifications as in Example 1, except that in the preparation of the laminate, the laminate was pressed at 25° C. with a roll press at a pressure of 20 kN / cm without heating.

[0087] <Comparative Example 3> In producing the laminate, a solid-state battery was obtained with the same specifications as in Example 1, except that the temperature when the laminate was hot-pressed (indicated as "pressing temperature" in the table) was set to the specifications shown in Table 1 (i.e., a temperature lower than the softening temperature of polymethyl methacrylate).

[0088] The thicknesses of the active material layer, intermediate layer, and resin current collector in the "positive electrode active material layer / intermediate layer / resin current collector / intermediate layer / negative electrode active material layer" structure of the solid-state battery of each example were measured by the method described above. The results are shown in Table 1. Note that the solid-state batteries of Comparative Example 2 and Comparative Example 3 were found to have no intermediate layer as a result of measurement by the method described above. In Table 1, the item "thickness ratio (intermediate layer / resin current collector)" refers to the thickness of the intermediate layer relative to the thickness of the resin current collector (intermediate layer / resin current collector).

[0089] <Evaluation of charging restraint pressure> The solid-state batteries of Example 1 and Comparative Example 1 were sandwiched between two restraining plates, and the two restraining plates were fastened with a fastener at a restraining pressure of 5 MPa to fix the distance between the two restraining plates. Next, this restrained laminate was charged at a constant current of 1 / 10 C to 8.10 V, and then charged at a constant voltage of 8.10 V to a cut-off current of 1 / 100 C. The restraining pressures before and after charging were recorded. The restraining pressure P BEFORE and the restraining pressure at the end of charging P AFTER Difference from (P BEFORE -P AFTER The absolute value of the confinement pressure fluctuation was divided by the discharge capacity to obtain the confinement pressure fluctuation value. A larger confinement pressure fluctuation value indicates a larger expansion of the solid-state battery during charging.

[0090] 2 is a graph showing the relationship between the confining pressure fluctuation value and the charge amount in Example 1 and Comparative Example 1. As shown in FIG. 2, the solid-state battery of Example 1 had a suppressed fluctuation in the confining pressure caused by charging, compared to the solid-state battery of Comparative Example 1.

[0091] <Evaluation of discharge capacity> Using a galvanostat, 50 cycles of charge / discharge tests were performed under the conditions of a current of 0.1C, a charge cutoff voltage of 8.10V, and a discharge cutoff voltage of 5.0V. Starting with charging, the amount of current required for discharging to 5.0V after one charge was calculated, and the amount was divided by the weight of the active material used in the measurement to calculate the discharge capacity in each cycle. The 50th discharge capacity was then divided by the first discharge capacity to obtain the capacity retention rate (%) after 50 cycles. The results are shown in Table 1.

[0092] Fig. 3 is a graph showing the relationship between the discharge capacity and the number of charge / discharge cycles in Example 1 and Comparative Example 1. As shown in Fig. 3, the solid-state battery of Example 1 is superior in capacity retention rate to the solid-state battery of Comparative Example 1, that is, it was found that the deterioration of cycle characteristics is suppressed.

[0093] <Evaluation of resistance value> The solid-state batteries of Example 1, Example 2, and Comparative Example 1 were sandwiched between two constraining plates, and the two constraining plates were clamped with a clamping tool at a constraining pressure of 5 MPa to fix the distance between the two constraining plates. Next, this constrained laminate was charged at a constant current of 1 / 10C to 8.10V, and then charged at a constant voltage of 8.10V to a cut-off current of 1 / 100C. Furthermore, a constant current discharge was performed at 1 / 10C to 5.0V, and then a constant voltage discharge was performed at 5.0V to a cut-off current of 1 / 100C. The resistance value was calculated by dividing the absolute value of the difference between the voltage before charging and the voltage after 0.1 seconds of discharge by the current equivalent to 1 / 100C. The obtained resistance value was shown in FIG. 4 as a relative value to the resistance value in the solid-state battery of Comparative Example 1. Fig. 4 is a graph showing the relationship between the relative resistance value and the thickness of the intermediate layer in the solid-state batteries of Example 1, Example 2, and Comparative Example 1. As shown in Fig. 4, it was found that the increase in resistance value caused by peeling of the active material layer from the current collector was suppressed in the solid-state batteries of the Examples, compared to the solid-state battery of Comparative Example 1.

[0094] [Table 1]

[0095] As shown in Table 1, it was found that the solid state batteries of the Examples were superior in capacity retention rate to the solid state batteries of the Comparative Examples, that is, the deterioration of cycle characteristics was suppressed. [Explanation of symbols]

[0096] A negative electrode active material layer B Solid electrolyte layer C positive electrode active material layer 101 Negative electrode active material 102 Solid electrolyte 103 Cathode active material 105, 107 Conductive additives 109, 111 Binder 113 Negative electrode current collector 115 Positive electrode current collector

Claims

1. A resin collector including a resin and a conductive material; An active material layer including an active material; and an intermediate layer interposed between the active material layer and the resin current collector, in which at least one component contained in the active material layer and at least one component contained in the resin current collector are mixed; A solid-state battery comprising an electrode having the

2. 2. The solid-state battery according to claim 1, wherein a thickness of the intermediate layer relative to a thickness of the resin current collector (intermediate layer / resin current collector) is 1 / 30 or more and 1 / 6 or less.

3. The solid-state battery according to claim 1 , wherein the active material comprises a Si-based active material.

4. The resin collector has a linear expansion coefficient of 200×10 -6 ppm / K or more 350×10 -6 The solid-state battery according to claim 1 or 2, wherein the concentration of ZnO in the solid-state battery is less than or equal to ppm / K.

5. A solid electrolyte layer including a solid electrolyte is provided.

3. The solid-state battery according to claim 1, wherein the softening temperature of the resin is equal to or lower than the crystallization temperature of the solid electrolyte.

6. 3. The solid-state battery of claim 1 or 2, wherein the conductive material comprises vapor grown carbon fiber (VGCF).

7. 1. A method for producing a solid-state battery, comprising: pressing a laminate in which a resin current collector containing a thermoplastic resin and a conductive material and an active material layer containing an active material are laminated together at a temperature equal to or higher than the softening temperature of the thermoplastic resin to produce an electrode.

Citation Information

Patent Citations

  • Electrode and method of manufacturing the same

    JP2010146901A

  • Manufacturing method of electrode for secondary battery

    JP2011060521A

  • Electrode for all-solid-state secondary batteries and method for producing same

    WO2013146916A1

  • Electrode

    WO2016031690A1

  • Positive electrode for lithium battery

    WO2016158754A1